Penerapan Metode Introspeksi dan Ekstrospeksi dalam Meningkatkan Kompetensi Penyuluh Agama - Yosep Sudarso (JURNAL ILMIAH NUSANTARA, 2025)
As ASN, religious counselor is required to have adequate competence. There are three competencies required of a religious counselor, namely managerial, socio-cultural and technical competencies related to understanding duties and functions and carrying them out professionally. However, the results of several studies show that many religious counselors do not have adequate competence. Therefore, efforts to increase competency are absolute. This research using the literature review method aims to introduce introspection and extrospection methods so that they can be applied by religious counselor to improve their competence. The essence of both methods is self-knowledge. Introspection means that the religious counselor assesses himself. Techniques that can be used include mindfulness, asking yourself, writing a journal, accepting yourself, and changing yourself. On the other hand, in the extrospection method, the religious counselor is assessed by other parties, including fellow religious counselor, members of the assisted group and the religious counselor's direct superior. Techniques used in extrospection include direct observation, interviews and case studies.